2022
DOI: 10.3389/fimmu.2022.987895
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic gastrointestinal disorders in patients with inborn errors of immunity: Data from the USIDNET registry

Abstract: RationaleEosinophilic gastrointestinal disorders (EGID), including eosinophilic esophagitis (EoE), are inflammatory disorders of the gastrointestinal mucosa mediated by complex immune mechanisms. Although there have been initial reports of EGID in patients with inborn errors of immunity (IEI), little is known about the presentation of EGID in immunodeficient individuals.MethodsWe queried the U.S. Immunodeficiency Network (USIDNET) for patient records including the terms eosinophilic esophagitis, gastritis, ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Recently, Tran et al reviewed the U.S. immunodeficiency Network (USIDNET), finding that 74 IEI patients had a concomitant diagnosis of EGID [ 23 ]. In this study, 61 patients were affected by EoE, and 27 (44.2%) had CVID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Tran et al reviewed the U.S. immunodeficiency Network (USIDNET), finding that 74 IEI patients had a concomitant diagnosis of EGID [ 23 ]. In this study, 61 patients were affected by EoE, and 27 (44.2%) had CVID.…”
Section: Discussionmentioning
confidence: 99%
“…EGIDs are clinically heterogeneous diseases with symptoms depending on the age at onset, the site of inflammation, response to treatments, and related comorbidities (allergic and not allergic), thus, defining a spectrum of different diseases [ 22 ]. Recently, data from the USIDNET reported that EGIDs are more commonly found in patients with different IEI, such as common variable immunodeficiency (CVID) (43.2%), chronic granulomatous disease (CGD) (8.1%), hyper-IgE syndrome (6.8%), and autoimmune lymphoproliferative syndrome (6.8%) [ 23 ]. Nevertheless, more research is needed to confirm these findings and understand if patients with EGIDs and IEI may have distinct clinical features, responses to therapies, and disease endotype.…”
Section: Eosinophilic Gastrointestinal Diseasesmentioning
confidence: 99%